»En mexicansk blondine der sparker røv« - Marie Højlund Bræmer; Thomas Friis Søgaard (Nordisk Tidsskrift for Kriminalvidenskab)
Abstract In recent decades, the selling and purchasing of illicit drugs has been increasingly mediated by use of communication technologies such as mobile phones and social media apps. While the risk of police intervention has traditionally restricted dealers’ use of advertisements to attract customers, the increasing technologization of retail-level drug markets has opened up new avenues for dealers’ use of proactive marketing. This article contributes to the understanding of current transformations of the retail-level drug market by providing insight into how drug dealers compete for and try to attract customers by use of strategic and targeted advertising. Based on an in-depth analysis of the textual and visual content of 99 illicit »drug commercials« circulated through SMS-based (Short Message Service) drug lines, we demonstrate how drug dealers draw on a number of psychological and cognitive techniques such as repetition, association, humour, hooks, slogans and storytelling, all of which are also found in legal marketing. We conclude by arguing that there is a need for more studies on how »drug commercials« affect drug users’ purchasing practices, including their choice of dealer.